결혼이주여성의 배우자지지, 가족지지가 정신건강에 미치는 영향 - 김순옥(Soon-Ok Kim); 임현숙(Hyun-Suk Lim); 정구철(Goo-Churl Jeong) (한국콘텐츠학회 논문지, 13(11), 2013)
By identifying the effects of support from spouse and family on the mental health of marriage immigrant women, this study was proposed in obtaining basic data for a mental health intervention program. This study is a descriptive correlation study conducted on 129 marriage immigrant women as subjects. The result of the study showed differences in the following: for anxiety, depending on their country of origin, length of marriage, family structure, marriage structure, visit back home, and Korean language skill; for depression, depending on their spouse's education level, providing financial support for family back home, and Korean language skill; for somatization disorder, depending on their spouses' education level, area of residence, and occupation. Also, anxiety and depression showed a negative correlation with support from spouse and family, and somatization disorder showed a negative correlation with support from family. The main variable for mental health was support from family; for anxiety, the main variables were country of origin, length of marriage, and marriage structure; for somatization disorder, the main variables were spouse's education level, area or residence, and occupation. Based on the results of this study, a variety of mental health programs helpful for immigrant women in adapting to their multi-faceted and complex life in a different culture and nursing interventions for improving support from family would need to be developed. 본 연구의 목적은 결혼이주여성의 배우자지지와 가족지지가 정신건강에 미치는 영향을 파악하여, 정신건강증진을 위한 중재프로그램의 기초자료로 활용하고자 실시하였다. 본 연구는 결혼이주여성 129명을 대상으로 실시한 서술적 상관관계 연구이다. 연구결과로 상태불안은 출신국가, 결혼기간, 가족형태, 결혼형태, 모국에 방문경험, 한국어 능력, 우울은 배우자학력, 친정에 경제적 지원, 한국어 능력, 신체화 장애는 배우자 학력, 거주 지역, 직업에서 차이가 있었다. 또 상태불안과 우울은 가족지지 및 배우자지지, 신체화 장애는 가족지지와 부적 상관관계가 있었다. 정신건강에 영향을 미치는 주요 변수는 가족지지였으며, 상태불안에는 출신국가, 결혼기간, 결혼형태, 한국어 능력, 신체화 장애에는 배우자학력과 거주 지역, 직업이었다. 본 연구 결과를 근거로 이주여성의 다면적이고 복합적인 이질문화생활에 적응을 도울 수 있는 다양한 정신건강교육 프로그램과 함께 가족지지 향상을 위한 간호학적 중재개발이 이루어져야 한다.